Fenologia, maturação fisiológica e aspectos da germinação de sementes de Platymiscium floribundum Vog. no Parque Estadual Alberto Löfgren, Instituto Florestal, São Paulo - SP - Silva, Maria Conceição Carvalho da (2005)
In this work was evaluated the seeds and fruits development of Plathymiscium floribundum Vog. and associated it with the phenophases, in order to get seeds with high physiological quality. The phenological observations were carried out using 20 matrix from Parque Estadual Alberto Löfgren belong to Instituto Florestal - SP, since January 2001 until December 2003. For the maturation study fruits and seeds were collected, and were realized determinations as physical, chemical parameters, physiology and color patterns. The data recorded showed that the flower and fruit production occurred at the spring, during the rainy season. Besides it, in several trees the flower production was not followed by fruit development. The total abscision of these organs was observed. The seed production occurred in periods longer than one year, and was restricted to some individuals. The fruits produced at 2002 did not reach the mature stage, and only two matrix produced flowers and fruits. During 2003 all the fruits were detached by abscision. The fruit color and the dry weight of the fruits and seeds are good indicators for the physiology maturity of the seeds. This work also evaluated the vigor of Plathymiscium floribundum Vog. seeds, fresh harvest with 8,97% of moisture and stored during 75 days at room environment inside paper bags. The determinations were done each 15 days and included: moisture content, rate and percentage germination, electrical conductivity (EC) accelerated aging (AA) and tetrazolium test (TZ). The experiments were carried out with four replications of 15 seeds. For the EC test the seeds were weight and after were put inside plastic cups with 75 mL of distilled water, during 24h at 25oC. The values obtained differ after storage during 15 days. The AA was realized at 40oC and 100% of R.U. during 6 and 24 h and a difference was only registered after storage during 75 days. For the TZ test the seeds were pre imbibed during 24h at 25oC, without pericarp and immersed in solution 1% concentrated. The seeds presented high physiological quality, and the decrease only occurred at the last storage period. In this research was also evaluated the maximum tolerance limits for water and salt stresses on Platymiscium floribundum seeds, imbibed in KCl, NaCl, mannitol and PEG 6000 solutions for salt and water stress, respectively with osmotic potentials: 0; -0,2; -0,4; -0,6; -0,8; and -1,0MPa. The experiments were carried out with four replications of 20 seeds germinated at 27°C, and continuous light The obtained data were submitted to variance analysis and Tukey test. A significance reduction on rate and percentage germination was registered at -0,2MPa and -0,6MPa, respectively, using mannitol solutions. When PEG solutions were used a significantly reduction on rate and germination percentage was at -0,4 MPa. When KCl and NaCl solutions were used a gradual reduction on germination percentage occurred. The highest values of rate and germination percentage were registered for seeds germinated in mannitol solutions, in all osmotic potentials. In relation to salt stress the reductions on rate and germination percentage occurred slightly, in contrast to water stress. A significantly decrease on germination percentage was verified at -0,4MPa, for both salt solutions. In relation to germination rate, the reduction was first detected at -0,6MPa and -0,8MPa for KCl and NaCl solutions, respectively. The maximal tolerance limit was the same, between -1,0 and -1,2MPa, for salt and water stress.